2021
DOI: 10.1007/s11010-021-04157-7
|View full text |Cite
|
Sign up to set email alerts
|

Human cardiac fibroblasts produce pro-inflammatory cytokines upon TLRs and RLRs stimulation

Abstract: Heart inflammation is one of the major causes of heart damage that leads to dilated cardiomyopathy and often progresses to end-stage heart failure. In the present study, we aimed to assess whether human cardiac cells could release immune mediators upon stimulation of Toll-like receptors (TLRs) and Retinoic acid-inducible gene (RIG)-I-like receptors (RLRs).Commercially available human cardiac fibroblasts and an immortalized human cardiomyocyte cell line were stimulated in vitro with TLR2, TLR3, and TLR4 agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Nevertheless, role of cardiac fibroblasts in promoting inflammation have attracted more attention recently. Cardiomyocytes [20], cardiac endothelial cells [21], cardiac fibroblasts [6,22,23], and cardiac infiltrates [24,25] were all reported to produce inflammatory cytokines that cause cardiac remodeling and dysfunction. Among them, IL-1β mainly comes from cardiac endothelial cells and cardiac fibroblasts and is strictly regulated by inflammasomes [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, role of cardiac fibroblasts in promoting inflammation have attracted more attention recently. Cardiomyocytes [20], cardiac endothelial cells [21], cardiac fibroblasts [6,22,23], and cardiac infiltrates [24,25] were all reported to produce inflammatory cytokines that cause cardiac remodeling and dysfunction. Among them, IL-1β mainly comes from cardiac endothelial cells and cardiac fibroblasts and is strictly regulated by inflammasomes [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…We found that CHIKV-infected hearts display a significant yet transient production of proinflammatory chemokines and cytokines. Interestingly, it has been shown that upon TLRs or RIG-I-like receptor stimulation, human cardiac fibroblasts can produce proinflammatory cytokines and induce an antiviral immune response (Li et al, 2021). Therefore, the CHIKV-infected cardiac fibroblasts may be contributing to this transient production of immune modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary saturated fatty acid induced NF-κB activation and nuclear translocation lead to the production of pro-inflammatory cytokines (IL-6, TNF-α and IL-1β). 31,32 The NF-κB signaling pathway is also a major contributor to MAFLD by mediating the activation of M1 macrophages. 33,34 Furthermore, stimulation of M1 macrophages with LPS activates NF-κB, which induces the expression of NOD-like receptor family 3 (NLRP3).…”
Section: Papermentioning
confidence: 99%